2016
DOI: 10.1097/opx.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Periorbital Tissues and Accessories of Children

Abstract: Ortho-k may lower the total number of bacteria in conjunctiva due to the use of solution and lenses, but the physiologic effect of this treatment on the types of normal flora in children was minimal and should not increase the risk of microbial keratitis in children with good compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Both studies identified high contamination rates in lens accessories, due to failure to clean and/or disinfect and replace regularly, which were frequently overlooked by patients/adult caregivers and ECPs. The presence of Gram-negative rods in contact lenses and accessories also indicated poor drying of hands after washing in ortho-k lens wearers [164]. These studies emphasise two critical areas that require attention from ECPs and patients: proper hand hygiene and lens and accessories care.…”
Section: Non-compliancementioning
confidence: 84%
See 1 more Smart Citation
“…Both studies identified high contamination rates in lens accessories, due to failure to clean and/or disinfect and replace regularly, which were frequently overlooked by patients/adult caregivers and ECPs. The presence of Gram-negative rods in contact lenses and accessories also indicated poor drying of hands after washing in ortho-k lens wearers [164]. These studies emphasise two critical areas that require attention from ECPs and patients: proper hand hygiene and lens and accessories care.…”
Section: Non-compliancementioning
confidence: 84%
“…• Inadequate hand washing [161,163] • Poor hand drying before handling lenses [161,163,164] • Storing of lens accessories in the bathroom [162,163] • Failure to replace the lens case monthly [161] • Failure to clean the lenses daily after use [161,163] • Failure to disinfect the lens accessories weekly [163] • Failure to adhere to aftercare schedule [161] • Rinsing lens or case in tap water [154,155] contact lens wear. Widespread use of antiseptics and disinfectants (cationic antimicrobials, including quaternary ammonium compounds and biguanides) in clinics and hospitals has led to growing concern about the emergence of disinfectant-resistant microorganisms [197].…”
Section: Disinfectants and Resistant-microorganismsmentioning
confidence: 99%
“…Overall, studies showed little impact on the usual members of the ocular microbiome, CNS, Corynebacterium and Propionibacterium , but there may be an increased risk for presence of potential pathogens, especially Gram‐negative bacteria . Some researchers have indicated that contact lens wear, in particular using rigid or ortho‐K lenses, may reduce the overall numbers present . In contrast, the numbers of CNS may be increased by use of contact lenses …”
Section: Use Of Contact Lensesmentioning
confidence: 99%
“…Some researchers have indicated that contact lens wear, in particular using rigid or ortho‐K lenses, may reduce the overall numbers present . In contrast, the numbers of CNS may be increased by use of contact lenses …”
Section: Use Of Contact Lensesmentioning
confidence: 99%
“…Compressive forces of the reverse geometry rigid lenses can disturb the corneal epithelium, and a too long overnight wear can potentially cause infectious keratitis. The previously obtained clinical data indicated that most microbiological infections associated with the use of the ortho-k lens resulted in a corneal scar and almost 10% eyes required surgical treatment [ 47 ].…”
Section: Early Intervention and Nonpharmacological Therapy Of Myopmentioning
confidence: 99%